Crude Aloe vera Gel Shows Antioxidant Propensities and Inhibits Pancreatic Lipase and Glucose Movement In Vitro - Urmeela Taukoorah; M. Fawzi Mahomoodally (Advances in Pharmacological Sciences)
Aloe vera gel (AVG) is traditionally used in the management of diabetes, obesity, and infectious diseases. The present study aimed to investigate the inhibitory potential of AVG against α-amylase, α-glucosidase, and pancreatic lipase activity in vitro. Enzyme kinetic studies using Michaelis-Menten (Km) and Lineweaver-Burk equations were used to establish the type of inhibition. The antioxidant capacity of AVG was evaluated for its ferric reducing power, 2-diphenyl-2-picrylhydrazyl hydrate scavenging ability, nitric oxide scavenging power, and xanthine oxidase inhibitory activity. The glucose entrapment ability, antimicrobial activity, and total phenolic, flavonoid, tannin, and anthocyanin content were also determined. AVG showed a significantly higher percentage inhibition (85.56±0.91) of pancreatic lipase compared to Orlistat. AVG was found to increase the Michaelis-Menten constant and decreased the maximal velocity (Vmax) of lipase, indicating mixed inhibition. AVG considerably inhibits glucose movement across dialysis tubes and was comparable to Arabic gum. AVG was ineffective against the tested microorganisms. Total phenolic and flavonoid contents were 66.06±1.14 (GAE)/mg and 60.95±0.97 (RE)/mg, respectively. AVG also showed interesting antioxidant properties. The biological activity observed in this study tends to validate some of the traditional claims of AVG as a functional food.